Electrochemical device and electronic device

By controlling the content of aluminum, sodium and niobium elements in the positive electrode active material layer of lithium-ion batteries, the structure of lithium-manganese oxides is optimized, and the specific capacity attenuation of lithium-ion batteries at high temperatures is solved, and the circulation and storage performance are improved , and reduces production costs.

CN119208560AActive Publication Date: 2024-12-27NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411321213.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-08-11
Publication Date
2024-12-27
Estimated Expiration
2041-08-11

AI Technical Summary

Technical Problem

Lithium-ion batteries exhibit severe specific capacity attenuation in high temperature environments, resulting in damage to the structure of the positive electrode active material, affecting stability and service life.

Method used

The content range of aluminum and sodium elements in the positive electrode active material layer (0.01≤A≤2, 0.001≤B≤1) and the addition of niobium and cobalt elements to the lithium manganese oxide are optimized. The crystal structure and surfactant crystal surface reduce Mn dissolution, improve the high-temperature cycling performance and storage capacity maintenance performance of electrochemical devices.

Benefits of technology

It significantly improves the circulation and storage performance of lithium-ion batteries at high temperatures, extends the service life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208560A_ABST
    Figure CN119208560A_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device, the electrochemical device comprises a positive electrode, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, the positive electrode active material layer comprises lithium manganese oxide, the lithium manganese oxide comprises an aluminum element and a sodium element, and based on the weight of the positive electrode active material, the weight of the aluminum element is less than that of the sodium element. The content of the aluminum element is A%, the content of the sodium element is B%, 0.01 < = A < = 2, and 0.001 < = B < = 1. According to the present invention, the cycle performance of the electrochemical device, especially the cycle performance under the high temperature condition, can be improved, and the high temperature storage performance of the electrochemical device can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application submitted to the State Intellectual Property Office on August 11, 2021, with application number 202180002480.3 and invention name “An electrochemical device and electronic device”. Technical Field

[0002] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art

[0003] Lithium-ion batteries have many advantages such as high volumetric and mass energy density, long cycle life, high nominal voltage, low self-discharge rate, small size, and light weight, and are widely used in the field of consumer electronics. With the rapid development of electric vehicles and mobile electronic devices in recent years, the market has put forward higher requirements for lithium-ion batteries, for example, lithium-ion batteries are required to be stable even in high temperature environments.

[0004] However, the specific capacity of current lithium-ion batteries decays seriously at high temperatures. This is because high temperatures cause side reactions inside lithium-ion batteries, which destroy the structure of the positive electrode active material and affect the stability and service life of lithium-ion batteries. Therefore, there is an urgent need for a lithium-ion battery with a long service life at high temperatures. Summary of the invention

[0005] The purpose of this application is to provide an electrochemical device and an electronic device to improve the high temperature cycle performance of the electrochemical device. The specific technical solution is as follows:

[0006] A first aspect of the present application provides an electrochemical device, comprising a positive electrode, the positive electrode comprising a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, the positive electrode active material layer comprising lithium manganese oxide, the lithium manganese oxide comprising aluminum and sodium elements, based on the weight of the positive electrode active material, the aluminum content is A%, the sodium content is B%, and 0.01≤A≤2, 0.001≤B≤1 is satisfied.

[0007] The positive electrode active material layer of the present application includes lithium manganese oxide, and the lithium manganese oxide includes aluminum and sodium elements. By controlling the content of aluminum and sodium elements within the above range, manganese (Mn) dissolution can be reduced, thereby improving the high temperature cycle performance of the electrochemical device. Without being limited to any theory, this may be because the aluminum element in the above content range can enhance the stability of the Mn-O bond in the lithium manganese oxide, improve the crystal structure of the lithium manganese oxide, and reduce the Jahn-Tellen effect of the manganese element; sodium element, as an impurity element, has almost no effect on the high temperature cycle performance of the electrochemical device when it is within the above content range. Therefore, on the whole, the present application can reduce Mn dissolution by controlling the content of aluminum and sodium elements within the above range, while reducing the influence of sodium elements on the positive electrode performance, thereby improving the cycle performance and storage capacity retention performance of the electrochemical device.

[0008] The lithium manganese oxide of the present application may include but is not limited to: modified LiMn2O4 (hereinafter referred to as modified LMO). The present application has no particular restrictions on the modification method of the lithium manganese oxide. For example, an aluminum-containing compound may be added during the synthesis of LiMn2O4, so that the lithium manganese oxide of the present application contains aluminum.

[0009] The positive electrode active material layer of the present application may be disposed on at least one surface of the positive electrode current collector, for example, the positive electrode active material layer is disposed on one surface of the positive electrode current collector, or the positive electrode active material layer is disposed on both surfaces of the positive electrode current collector.

[0010] In one embodiment of the present application, the electrochemical device of the present application satisfies at least one of the conditions (a) or (b): (a) 0.011≤A+B≤2.5; (b) 0.1≤A / B≤125.

[0011] In one embodiment of the present application, 0.03≤A+B<2, 2<A / B≤125.

[0012] By controlling the sum of the aluminum content and the sodium content in the positive electrode active material, that is, the value of A+B is within the above range, and / or controlling the ratio of the aluminum content to the sodium content in the positive electrode active material, that is, the value of A / B is within the above range, an electrochemical device with excellent high-temperature cycle performance and storage capacity retention performance can be obtained.

[0013] In one embodiment of the present application, the lithium manganese oxide of the present application further comprises niobium element, and the content of niobium element is C% based on the weight of the positive electrode active material, satisfying 0﹤C≤1.

[0014] Without being limited to any theory, the inventors of the present application have found that the niobium element within the above content range can further improve the crystal structure of the lithium manganese oxide, so that the number of active crystal faces (111) of the lithium manganese oxide exposed on the outer surface is reduced, that is, the number of active crystal faces (111) in contact with the electrolyte is reduced, thereby reducing the side reaction between the electrolyte and the surface of the lithium manganese oxide, further reducing the dissolution of Mn, and thus improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device. In the process of modifying the lithium manganese oxide, the content of the niobium element in the positive electrode active material layer can be controlled by adding a niobium-containing compound and controlling the addition amount of the niobium-containing compound.

[0015] In one embodiment of the present application, the electrochemical device of the present application satisfies at least one of the conditions (c) to (d): (c) 0.011 < A + C ≤ 2.8; (d) 0.011 ≤ A + B + C ≤ 3.3; (e) 0 < C / B ≤ 40. Without being limited to any theory, by controlling the sum of the contents of aluminum and niobium in the positive electrode active material, that is, the value of A + C within the above range, and / or, controlling the sum of the contents of aluminum, sodium and niobium in the positive electrode active material, that is, the value of A + B + C within the above range, and / or, controlling the ratio of the niobium content to the sodium content in the positive electrode active material, that is, the value of C / B within the above range, an electrochemical device with excellent high temperature cycle performance and storage capacity retention performance can be obtained.

[0016] In one embodiment of the present application, 0.07≤A+C≤2.3.

[0017] By controlling the sum of the aluminum and niobium contents in the positive electrode active material, that is, the value of A+C within the above range, better high temperature cycle performance and storage capacity retention performance can be obtained. In one embodiment of the present application, when the positive electrode plate powder of the present application is tested by X-ray diffraction (XRD), the lithium manganese oxide satisfies at least one of the conditions (f) to (g): (f) the lithium manganese oxide has a first diffraction peak corresponding to the (111) crystal plane at 18° to 20°, and the peak intensity of the first diffraction peak is I(111); (g) the lithium manganese oxide has a second diffraction peak corresponding to the (400) crystal plane at 43° to 45°, and the peak intensity of the second diffraction peak is I(400); (h) the lithium manganese oxide has a third diffraction peak corresponding to the (440) crystal plane at 63° to 65°, and the peak intensity of the third diffraction peak is I(440).

[0018] In one embodiment of the present application, the electrochemical device of the present application satisfies at least one of the conditions (i) to (j): (i) 0.25﹤I(400) / I(111)﹤0.55; (j) 0.35﹤I(440) / I(400)﹤0.55.

[0019] Without being limited to any theory, the inventors of the present application have found that by controlling I(400) / I(111) within the above range, and / or controlling I(440) / I(400) within the above range, the crystal structure of the lithium manganese oxide can be further improved, so that the number of active crystal faces (111) of the lithium manganese oxide exposed on the outer surface is reduced, thereby reducing the side reaction between the electrolyte and the surface of the lithium manganese oxide, further reducing Mn dissolution, and improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0020] In one embodiment of the present application, the positive electrode active material layer may further include lithium nickel cobalt manganese oxide, and the weight percentage of the cobalt element is less than or equal to 15% based on the weight of the positive electrode active material.

[0021] The positive electrode active material layer of the present application may also contain lithium nickel cobalt manganese oxide. The residual alkali (such as Li2CO3 or LiOH) on the surface of the lithium nickel cobalt manganese oxide can react with hydrofluoric acid (HF) in the electrolyte to reduce the acidity of the electrolyte, further reduce the dissolution of Mn, and thus improve the high temperature cycle performance and storage capacity retention performance of the electrochemical device. Therefore, based on the weight of the positive electrode active material in the present application, the weight percentage of cobalt in the positive electrode active material is controlled to be less than or equal to 15%, which can further improve the high temperature cycle performance and storage capacity retention performance of the electrochemical device while reducing the production cost.

[0022] In one embodiment of the present application, the molar ratio of nickel element to manganese element in the positive electrode active material layer is 0.02:1 to 0.7:1, and the molar ratio of cobalt element to manganese element is less than or equal to 0.3:1.

[0023] By controlling the molar ratio of nickel element to manganese element and the molar ratio of cobalt element to manganese element in the positive electrode active material layer within the above-mentioned range, the nickel element, manganese element and cobalt element in the positive electrode active material layer can be rationally configured, thereby obtaining an electrochemical device with excellent high-temperature cycle performance and storage capacity retention performance.

[0024] In one embodiment of the present application, the positive electrode active material layer may further include lithium iron phosphate (LiFePO4, ie, LFP), wherein the average particle size of the lithium iron phosphate is smaller than the average particle size of the lithium manganese oxide.

[0025] Without being limited to any theory, due to the small particle size of lithium iron phosphate, lithium iron phosphate is present on at least part of the surface of the lithium manganese oxide, that is, the lithium manganese oxide can be partially or completely coated with lithium iron phosphate, thereby inhibiting side reactions on the surface of the lithium manganese oxide and further improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0026] In one embodiment of the present application, the molar ratio of the iron element to the manganese element in the positive electrode active material layer is 0.02:1 to 0.25:1.

[0027] By controlling the molar ratio of iron to manganese in the positive electrode active material layer within the above range, the iron and manganese elements in the positive electrode active material layer can be rationally configured, and the side reactions on the surface of lithium manganese oxide can be suppressed, thereby further improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0028] In one embodiment of the present application, based on the weight of the positive electrode active material layer, the weight percentage of lithium iron phosphate is ≤30%.

[0029] Without being limited to any theory, when the content of lithium iron phosphate in the positive electrode active material layer is too high (e.g., higher than 30%), the energy density of the electrochemical device is affected. By controlling the weight percentage of lithium iron phosphate in the positive electrode active material layer within the above range, the electrochemical device can have a high energy density while further improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0030] In one embodiment of the present application, the compaction density P of the positive electrode active material layer is 2.7 g / cm 3 ≤P≤4.0g / cm 3 Without being limited to any theory, when the compaction density of the positive electrode active material layer is too low (e.g., less than 2.7 g / cm 3 ), which is not conducive to improving the energy density of the electrochemical device; when the compaction density of the positive electrode active material layer is too high (for example, higher than 4.0 g / cm 3 ), the positive electrode is more likely to be brittle, which is not conducive to the safety of the electrochemical device. By controlling the compaction density of the positive electrode active material layer within the above range, the electrochemical device can have high energy density and excellent safety.

[0031] The present application provides an electrochemical device and an electronic device, wherein the positive electrode of the electrochemical device comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises lithium manganese oxide, wherein the lithium manganese oxide comprises aluminum and sodium elements, and by controlling the aluminum content A% and the sodium content B% in the positive electrode active material to satisfy 0.01≤A≤2, 0.001≤B≤1, the crystal structure of the lithium manganese oxide can be improved, the dissolution of the manganese element can be reduced, the cycle performance of the electrochemical device can be improved, especially the cycle performance under high temperature conditions, and the high temperature storage performance of the electrochemical device can also be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the present application and the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present application.

[0033] Figure 1 This is the XRD diagram of the positive electrode plate powder of Example 35 of the present application. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other technical schemes obtained by ordinary technicians in the field belong to the scope of protection of the present application.

[0035] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0036] The first aspect of the present application provides an electrochemical device, comprising a positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising lithium manganese oxide, the lithium manganese oxide comprising aluminum and sodium, based on the total weight of the positive electrode active material, the aluminum content is A%, the sodium content is B%, and 0.01≤A≤2, 0.001≤B≤1. In one embodiment of the present application, 0.49≤A≤1.8, 0.001≤B﹤0.5.

[0037] The positive electrode active material layer of the present application includes lithium manganese oxide, and the lithium manganese oxide includes aluminum and sodium elements. By controlling the content of aluminum and sodium elements within the above range, manganese (Mn) dissolution can be reduced, thereby improving the high temperature cycle performance of the electrochemical device. Without being limited to any theory, this may be because the aluminum element in the above content range can enhance the stability of the Mn-O bond in the lithium manganese oxide, improve the crystal structure of the lithium manganese oxide, and reduce the Jahn-Tellen effect of the manganese element; sodium element, as an impurity element, has almost no effect on the high temperature cycle performance of the electrochemical device when it is within the above content range. Therefore, on the whole, the present application can reduce Mn dissolution by controlling the content of aluminum and sodium elements within the above range, while reducing the influence of sodium elements on the positive electrode performance, thereby improving the cycle performance and storage capacity retention performance of the electrochemical device.

[0038] The lithium manganese oxide of the present application may include but is not limited to: modified LiMn2O4 (hereinafter referred to as modified LMO). The present application has no particular restrictions on the modification method of the lithium manganese oxide. For example, an aluminum-containing compound may be added during the synthesis of LiMn2O4, so that the lithium manganese oxide of the present application contains aluminum.

[0039] The positive electrode active material layer of the present application may be disposed on at least one surface of the positive electrode current collector, for example, the positive electrode active material layer is disposed on one surface of the positive electrode current collector, or the positive electrode active material layer is disposed on both surfaces of the positive electrode current collector.

[0040] In one embodiment of the present application, the electrochemical device of the present application satisfies at least one of the conditions (a) or (b): (a) 0.011≤A+B≤2.5; (b) 0.1≤A / B≤125. In some embodiments, A+B can be 0.011, 0.03, 0.05, 0.07, 0.1, 0.3, 0.5, 0.9, 1.0, 1.1, 1.3, 1.5, 1.7, 1.9, 2.0, 2.5, or a range consisting of any two of the above values. In one embodiment of the present application, A / B can be 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, 3.0, 5.0, 7.0, 10, 15, 20, 25, 40, 60, 80, 100, 110, 120, 125, or a range consisting of any two of the above values.

[0041] Without being limited to any theory, the present application controls the sum of the aluminum content and the sodium content in the positive electrode active material, that is, the value of A+B is within the above range, and / or controls the ratio of the aluminum content to the sodium content in the positive electrode active material, that is, the value of A / B is within the above range, so as to obtain an electrochemical device with excellent high-temperature cycle performance and storage capacity retention performance. When A / B is too large, the cycle performance of the electrochemical device is limited. When the value of A / B is too small, it may affect the reversible capacity of the electrochemical device.

[0042] In one embodiment of the present application, the lithium manganese oxide further comprises niobium, and the content of niobium is C%, based on the total weight of the positive electrode active material, satisfying 0﹤C≤1. In some embodiments, 0.0001≤C≤0.7. In some embodiments, 0.0001≤C≤0.5. In some embodiments, C can be 0.001, 0.003, 0.005, 0.008, 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, or a range consisting of any two of the above values.

[0043] Without being limited to any theory, the inventors of the present application have found that the niobium element within the above content range can further improve the crystal structure of the lithium manganese oxide, so that the number of active crystal faces (111) of the lithium manganese oxide exposed on the outer surface is reduced, that is, the number of active crystal faces (111) in contact with the electrolyte is reduced, thereby reducing the side reaction between the electrolyte and the surface of the lithium manganese oxide, further reducing the dissolution of Mn, thereby improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device. In the process of lithium manganese oxide modification, the content of niobium in the positive electrode active material layer can be controlled by adding niobium-containing compounds and controlling the addition amount of niobium-containing compounds. The present application has no particular restrictions on niobium-containing compounds, for example, it can include but is not limited to: Nb2O5, NbF5.

[0044] In one embodiment of the present application, the electrochemical device of the present application satisfies the condition 0.01 < A + C ≤ 2.8. In some embodiments, 0.011 < A + C ≤ 2. In some embodiments, 0.07 < A + C ≤ 2.3. In some embodiments, 0.01 < A + C ≤ 1.6. In some embodiments, A + C can be 0.011, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8 or a range consisting of any two of the above values.

[0045] By controlling the sum of the contents of aluminum and niobium in the positive electrode active material, that is, the value of A+C is within the above range, the performance of the electrochemical device is in a better state. When the value of A+C is too high, the improvement in the cycle performance of the electrochemical device is limited and may affect the reversible capacity of the electrochemical device.

[0046] In one embodiment of the present application, the electrochemical device of the present application satisfies the condition 0.011≤A+B+C≤3.3, in some embodiments 0.1≤A+B+C≤2.0. In some embodiments A+B+C can be 0.011, 0.05, 0.07, 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.5, 3.0, 3.3 or a range consisting of any two of the above values.

[0047] By controlling the value of A+B+C within the above range, the electrochemical device has better cycle performance and storage performance.

[0048] In one embodiment of the present application, the electrochemical device of the present application satisfies the condition 0<C / B≤40. In some embodiments, 0﹤C / B≤10. In some embodiments, 0﹤C / B≤5. In some embodiments, 0<C / B≤3. In some embodiments, C / B can be 0.0001, 0.0005, 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, 1.2, 1.5, 1.7, 1.9, 2.0, 3.0, 5.0, 7.0, 9.0, 10.0, 15, 20, 25, 30, 35, 40 or a range consisting of any two of the above values.

[0049] By controlling the C / B value within the above range, an electrochemical device with excellent high-temperature cycle performance and storage capacity retention performance can be obtained. When the C / B value is too high, the cycle performance of the electrochemical device may be affected. When the C / B value is too low, the protection of the active crystal plane (111) of the lithium manganese oxide is small, the inhibition of Mn dissolution is limited, and the loss of reversible capacity of the electrochemical device may increase.

[0050] In one embodiment of the present application, when the positive electrode plate powder of the present application is tested by X-ray diffraction (XRD), the lithium manganese oxide shows a first diffraction peak corresponding to the (111) crystal plane at 18° to 20°, and the peak intensity of the first diffraction peak is I(111).

[0051] In one embodiment of the present application, when the positive electrode plate powder of the present application is tested by X-ray diffraction (XRD), the lithium manganese oxide shows a second diffraction peak corresponding to the (400) crystal plane at 43° to 45°, and the peak intensity of the second diffraction peak is I(400).

[0052] In one embodiment of the present application, when the positive electrode plate powder of the present application is tested by X-ray diffraction (XRD), the lithium manganese oxide shows a third diffraction peak corresponding to the (440) crystal plane at 63° to 65°, and the peak intensity of the third diffraction peak is I(440).

[0053] The positive electrode plate of the present application includes a positive electrode active material layer, which contains a positive electrode active material. The main component of the positive electrode active material is lithium manganese oxide. XRD testing shows that the lithium manganese oxide of the present application contains (111) crystal planes, (400) crystal planes and (440) crystal planes.

[0054] In one embodiment of the present application, the electrochemical device of the present application satisfies 0.25﹤I(400) / I(111)﹤0.55.

[0055] In one embodiment of the present application, the electrochemical device of the present application satisfies 0.35﹤I(440) / I(400)﹤0.55.

[0056] Without being limited to any theory, by controlling I(400) / I(111) within the above range, and / or controlling I(440) / I(400) within the above range, the crystal structure of the lithium manganese oxide can be further improved, so that the number of active crystal faces (111) of the lithium manganese oxide exposed on the outer surface is reduced, thereby reducing the side reaction between the electrolyte and the surface of the lithium manganese oxide, further reducing Mn dissolution, and improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0057] In one embodiment of the present application, the positive electrode active material further comprises an M element, and the M element comprises at least one of Cu, Fe, Mg, Ti, Zr, Zn, W, Sr, and Y. In some embodiments, the M element may comprise Mg and at least one of Cu, Fe, Ti, Zr, Zn, W, Sr, and Y.

[0058] In one embodiment of the present application, based on the weight of the positive electrode active material, the content of the M element is less than or equal to 5%. In some embodiments, the content of the M element can be 0.01%, 0.03%, 0.05%, 0.07%, 0.1%, 0.3%, 0.5%, 0.7%, 1.0%, 2.0%, 3.0%, 5.0% or a range consisting of any two of the above values.

[0059] In one embodiment of the present application, the positive electrode active material further includes an X element, and the X element includes at least one of S, P, B, F, or Cl.

[0060] In one embodiment of the present application, based on the weight of the positive electrode active material, the content of element X is less than or equal to 3%. In some embodiments, the content of element X can be 0.01%, 0.03%, 0.05%, 0.07%, 0.1%, 0.3%, 0.5%, 0.7%, 1.0%, 2.0%, 3.0% or a range consisting of any two of the above values.

[0061] In one embodiment of the present application, the positive electrode active material layer may further include lithium nickel cobalt manganese oxide, and the weight percentage of cobalt is less than or equal to 15% based on the weight of the positive electrode active material.

[0062] Without being limited to any theory, the positive electrode active material layer of the present application may also include lithium nickel cobalt manganese oxide. The residual alkali (such as Li2CO3 or LiOH) on the surface of the lithium nickel cobalt manganese oxide can react with hydrofluoric acid (HF) in the electrolyte to reduce the acidity of the electrolyte, further reduce Mn dissolution, and thus improve the high temperature cycle performance and storage capacity retention performance of the electrochemical device. When the cobalt content is too high, it will lead to an increase in the production cost of the electrochemical device. Therefore, in the present application, based on the weight of the positive electrode active material, the weight percentage of cobalt in the lithium nickel cobalt manganese oxide is controlled to be less than or equal to 15%, which can further improve the high temperature cycle performance and storage capacity retention performance of the electrochemical device while reducing the production cost.

[0063] The present application has no particular restrictions on the lithium nickel cobalt manganese oxide, as long as the purpose of the present application can be achieved. For example, the lithium nickel cobalt manganese oxide can be lithium nickel cobalt manganese oxide (hereinafter referred to as NCM). The lithium nickel cobalt manganese oxide can be single crystal lithium nickel cobalt manganese oxide or polycrystalline lithium nickel cobalt manganese oxide.

[0064] In one embodiment of the present application, the molar ratio of nickel element to manganese element in the positive electrode active material layer is 0.02:1 to 0.7:1.

[0065] In one embodiment of the present application, the molar ratio of the cobalt element to the manganese element in the positive electrode active material layer is less than or equal to 0.3:1.

[0066] In the present application, by controlling the molar ratio of nickel element to manganese element and the molar ratio of cobalt element to manganese element in the positive electrode active material layer within the above-mentioned range, the nickel element, manganese element and cobalt element in the positive electrode active material layer can be reasonably configured, thereby obtaining an electrochemical device with excellent high-temperature cycle performance and storage capacity retention performance.

[0067] In one embodiment of the present application, the positive electrode active material layer may further include lithium iron phosphate (LiFePO4, ie, LFP), wherein the average particle size of the lithium iron phosphate is smaller than the average particle size of the lithium manganese oxide.

[0068] In one embodiment of the present application, the average particle size of the lithium iron phosphate is less than or equal to 2 μm. In some embodiments, the average particle size of the lithium iron phosphate is less than or equal to 1.8 μm. In some embodiments, the average particle size of the lithium iron phosphate is less than or equal to 1.5 μm. In some embodiments, the average particle size of the lithium iron phosphate is less than or equal to 1.2 μm. In some embodiments, the average particle size of the lithium iron phosphate is less than or equal to 1.0 μm.

[0069] One implementation scheme of the present application utilizes the small particle size of lithium iron phosphate so that at least part of the surface of the lithium manganese oxide has lithium iron phosphate, that is, the lithium manganese oxide can be partially coated with lithium iron phosphate or completely coated, thereby inhibiting side reactions on the surface of the lithium manganese oxide and further improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0070] In one embodiment of the present application, the molar ratio of iron to manganese in the positive electrode active material layer is 0.02:1 to 0.25:1. In some embodiments, the molar ratio of iron to manganese in the positive electrode active material layer is 0.03:1 to 0.13:1. In some embodiments, the molar ratio of iron to manganese in the positive electrode active material layer is 0.05:1 to 0.12:1. In some embodiments, the molar ratio of iron to manganese in the positive electrode active material layer is 0.03:1 to 0.13:1.

[0071] By controlling the molar ratio of iron to manganese in the positive electrode active material layer within the above range, the iron and manganese elements in the positive electrode active material layer can be rationally configured, and the side reactions on the surface of lithium manganese oxide can be suppressed, thereby further improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0072] In one embodiment of the present application, based on the weight of the positive electrode active material layer, the weight percentage of lithium iron phosphate is ≤30%.

[0073] Without being limited to any theory, when the content of lithium iron phosphate in the positive electrode active material layer is too high (e.g., higher than 30%), the energy density of the electrochemical device is affected. By controlling the weight percentage of lithium iron phosphate in the positive electrode active material layer within the above range, the electrochemical device can have a high energy density while further improving the high temperature cycle performance and storage capacity retention performance of the electrochemical device.

[0074] In one embodiment of the present application, the compaction density P of the positive electrode active material layer is 2.7 g / cm 3 ≤P≤4.0g / cm 3 Without being limited to any theory, when the compaction density of the positive electrode active material layer is too low (e.g., less than 2.7 g / cm 3 ), which is not conducive to improving the energy density of the electrochemical device; when the compaction density of the positive electrode active material layer is too high (for example, higher than 4.0 g / cm 3 ), the positive electrode is more likely to be brittle, which is not conducive to the safety of the electrochemical device. By controlling the compaction density of the positive electrode active material layer within the above range, the electrochemical device can have high energy density and excellent safety.

[0075] The present application does not have any particular restrictions on the preparation method of lithium manganese oxide, and a preparation method known to those skilled in the art can be used. For example, in the process of synthesizing lithium manganese oxide, an aluminum-containing compound (such as Al2O3, Al(OH)3, AlF3) can be added to LiMn2O4 to obtain the above-mentioned lithium manganese oxide, that is, modified LMO. In addition, the present application can achieve the change of the aluminum element in the positive electrode active material layer by adjusting the content of the aluminum element in the lithium manganese oxide, such as controlling the amount of the aluminum-containing compound added; by adjusting the content of the sodium element in the precursor of LiMn2O4, the change of the sodium element content in the positive electrode active material layer can be achieved. The present application does not specifically limit the adjustment process, as long as the purpose of the present application can be achieved.

[0076] There is no particular limitation on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer. Among them, the positive electrode current collector is not particularly limited and can be any positive electrode current collector in the art, such as aluminum foil, aluminum alloy foil or composite current collector.

[0077] There are no special restrictions on the negative electrode plate in the present application, as long as the purpose of the present application can be achieved. For example, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer. Among them, the negative electrode current collector is not particularly limited, and materials such as metal foil or porous metal plate can be used, such as foil or porous plate of metals such as copper, nickel, titanium or iron or their alloys, such as copper foil. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and a thickener. There are no special restrictions on the negative electrode active material, and any negative electrode active material in the art can be used. For example, it can include artificial graphite, natural graphite, mesophase carbon microbeads (MCMB), soft carbon, hard carbon, silicon, silicon carbon, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium; the conductive agent may be at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers; the binder may be at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin or carboxymethyl cellulose (CMC); the thickener may be carboxymethyl cellulose (CMC).

[0078] The substrate of the isolation film of the present application includes, but is not limited to, at least one selected from polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyimide (PI) or aramid. For example, polyethylene includes at least one component selected from high-density polyethylene, low-density polyethylene and ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have excellent effects on preventing short circuits and can improve the stability of electrochemical devices through the shutdown effect. The substrate can be a single-layer structure or a multi-layer composite structure of a plurality of mixtures, with a thickness of 3μm to 20μm.

[0079] The lithium ion battery of the present application also includes an electrolyte, which may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, wherein the electrolyte includes a lithium salt and a non-aqueous solvent. In some embodiments of the present application, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, the lithium salt may be selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents, or a combination thereof. The above-mentioned carbonate compound may be a chain carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound, or a combination thereof. Examples of the above-mentioned linear carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate and combinations thereof. Examples of the above-mentioned carboxylic acid ester compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone, caprolactone and combinations thereof. Examples of the above-mentioned ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran and combinations thereof. Examples of the above-mentioned other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphates and combinations thereof.

[0080] A second aspect of the present application provides an electronic device comprising the electrochemical device described in the above embodiments of the present application.

[0081] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0082] The preparation process of the electrochemical device is well known to those skilled in the art and is not particularly limited in this application. For example, a lithium-ion battery can be manufactured by overlapping the positive electrode and the negative electrode via a separator, and placing them in a housing after winding, folding, etc. as required, injecting an electrolyte into the housing and sealing it. In addition, an overcurrent protection element, a guide plate, etc. can also be placed in the housing as required to prevent the pressure inside the lithium-ion battery from rising and overcharging and discharging.

[0083] The present application provides an electrochemical device and an electronic device, wherein the positive electrode of the electrochemical device comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises lithium manganese oxide, wherein the lithium manganese oxide comprises aluminum and sodium elements, and by controlling the aluminum content A% and the sodium content B% in the positive electrode active material to satisfy 0.01≤A≤2, 0.001≤B≤1, the crystal structure of the lithium manganese oxide can be improved, the dissolution of the manganese element can be reduced, the cycle performance of the electrochemical device can be improved, especially the cycle performance under high temperature conditions, and the high temperature storage performance of the electrochemical device can also be improved.

[0084] Test methods and equipment:

[0085] Element content test of positive electrode active material layer:

[0086] The lithium-ion battery discharged to a voltage of 2.8V was disassembled, and then the positive electrode active material layer on the dried positive electrode plate was dissolved with a mixed solvent (for example, 0.4g of positive electrode active material was dissolved in a mixed solvent of 10ml (nitric acid and hydrochloric acid mixed in a ratio of 1:1) aqua regia and 2ml HF), the volume was fixed to 100mL, and then an ICP (Inductively coupled plasma) analyzer was used to test the content of elements such as Al, Na, and Nb in the solution.

[0087] XRD test:

[0088] The lithium-ion battery discharged to a voltage of 2.8V is disassembled, and then the positive electrode plate is taken out, and the positive electrode active material layer is scraped off with a scraper to obtain the positive electrode active material layer powder, and then the positive electrode active material layer powder is placed in the sample stage of an XRD test instrument (model Bruker, D8), and a scanning rate of 2° / min and a scanning angle range of 10° to 90° are used to obtain an XRD diffraction pattern. In the XRD diffraction pattern, the peak values ​​corresponding to the characteristic peaks (111), (400), and (440) of lithium manganese oxide are taken, and then the ratio of I(400) to I(111) is obtained, which is recorded as I(400) / I(111); the ratio of I(440) to I(400) is recorded as I(440) / I(400).

[0089] Particle size test in the positive electrode active material layer:

[0090] The lithium-ion battery discharged to a voltage of 2.8V was disassembled, and the dried positive electrode was sliced. The cross-section of the slice was observed using a scanning electron microscope (SEM) to find the particles in the cross-section. The composition of the single particle was determined using an energy dispersive spectrometer (EDS). The size of the single particle was measured using SEM at a magnification of 1000 times. Three pictures were selected and the average value was calculated. The test instrument was OXFORD EDS (X-max-20mm 2 ).

[0091] Positive electrode active material layer compaction density test:

[0092] The lithium-ion battery discharged to a voltage of 2.8V was disassembled, and then the positive electrode sheet was taken out, and the positive electrode sheet was soaked in DMC (dimethyl carbonate) for 30 minutes to remove the electrolyte and by-products on the surface of the positive electrode sheet, and then dried in a fume hood for 4 hours. The dried positive electrode sheet was taken out, and 5 positive electrode sheets of 5 cm×5 cm were selected. The thickness of the positive electrode sheet was measured by a micrometer, which was recorded as d0; the positive active material layer in the positive electrode sheet was scraped off with a scraper, and the weight of the positive active material layer was weighed by a balance, which was recorded as m. The thickness of the current collector after removing the active material was measured by a micrometer, which was recorded as d, and the compaction density of the positive active material layer was calculated according to the following formula:

[0093] Compacted density P = m / [5cm×5cm×(d0-d)], unit: g / cm 3 .

[0094] The compaction density of the positive electrode active material layer is the average value of 5 positive electrode sheets.

[0095] Lithium-ion battery capacity test:

[0096] Take 4 lithium-ion batteries and charge them at a charging current of 0.5C in an environment of 25°C until the upper limit voltage is 4.2V. Then, discharge them at a constant current of 0.2C until the final voltage is 2.8V. Calculate the first discharge capacity at 0.2C as the capacity of the lithium-ion battery.

[0097] Lithium-ion battery cycle performance test:

[0098] The lithium-ion battery is repeatedly charged and discharged through the following steps, and the discharge capacity retention rate of the lithium-ion battery is calculated:

[0099] In an environment of 25°C, the first charge and discharge were carried out. Charging was carried out at a charging current of 0.5C until the voltage was 4.2V, and then constant current discharge was carried out at a discharge current of 1C until the final voltage was 2.8V. The discharge capacity was recorded as the discharge capacity of the first cycle. The above steps were then repeated for 1000 charge and discharge cycles, and the discharge capacity of the 1000th cycle was recorded.

[0100] 25° C. cycle capacity retention rate=(discharge capacity at the 1000th cycle / discharge capacity at the first cycle)×100%.

[0101] In an environment of 45°C, charge at a charging current of 0.5C until the voltage is 4.2V, then discharge at a constant current of 1C until the final voltage is 2.8V, and record the discharge capacity as the discharge capacity of the first cycle; then repeat the above steps for 500 charging and discharging cycles, and record the discharge capacity of the 500th cycle.

[0102] 45° C. cycle capacity retention rate=(discharge capacity at the 500th cycle / discharge capacity at the first cycle)×100%.

[0103] Lithium-ion battery high temperature storage performance test:

[0104] In an environment of 25°C, charge at a charging current of 0.5C until the upper limit voltage is 4.2V, then discharge at a constant current of 1C until the final voltage is 2.8V, and record the discharge capacity as the capacity before storage;

[0105] Charge at a constant current of 0.5C rate to a voltage of 3.85V, charge at a constant voltage of 4.2V until the current is less than 0.05C, store the battery in a 60°C oven for 14 days, and then discharge at a constant current of 1C until the final voltage is 2.8V; then charge at a charging current of 0.5C until the voltage is 4.2V, and then discharge at a constant current of 1C until the voltage is 2.8V, and record the battery discharge capacity as the capacity after storage.

[0106] Capacity retention rate of lithium-ion battery = capacity after storage / capacity before storage × 100%.

[0107] Example 1

[0108] <Preparation of lithium manganese oxide>

[0109] Weigh 203.3 g of lithium carbonate (wherein the lithium content is 18.71%), 1000.0 g of manganese dioxide (wherein the Mn content is 60.22% and the Na content is 0.27%), and 29.96 g of aluminum oxide (wherein the aluminum content is 52.91%), mix them in a high-speed mixer at 300 r / min for 20 min, place the mixture in an air kiln, heat it to 820° C. at 5° C. / min, keep it for 24 h, take it out after natural cooling, and pass it through a 300-mesh sieve to obtain lithium manganese oxide (i.e., modified LMO).

[0110] <Preparation of positive electrode sheet>

[0111] The prepared positive electrode active material, binder polyvinylidene fluoride (PVDF), conductive carbon black, and carbon nanotubes (CNT) are mixed in a weight ratio of 95:2:1.8:1.2, and then NMP (N-methylpyrrolidone) is added as a solvent, and a uniform and transparent positive electrode slurry with a solid content of 75% is prepared under vacuum stirring. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 9μm, dried at 90°C, and cold pressed to obtain a positive electrode sheet with a total thickness of 100μm for the positive electrode active material layer, and then the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a positive electrode active material layer coated on both sides. The positive electrode sheet is cut into a specification of 74mm×867mm and welded to the pole ear for standby use. Among them, the aluminum content in the positive electrode active material layer is 1.52%, the sodium content is 0.26%, and the compaction density of the positive electrode active material layer is 2.8g / cm 3 .

[0112] <Preparation of negative electrode sheet>

[0113] The negative electrode active material artificial graphite, styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a weight ratio of 98:1:1, and then deionized water is added as a solvent to prepare a slurry with a solid content of 70%, and stirred evenly. The slurry is evenly coated on one surface of a copper foil with a thickness of 8μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a negative electrode active material layer with a thickness of 150μm, and then the above coating steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. The negative electrode sheet is cut into a specification of 74mm×867mm and welded to the pole ear for standby use.

[0114] <Preparation of Separator Film>

[0115] A polyethylene (PE) porous polymer film with a thickness of 15 μm was used as the isolation membrane.

[0116] <Preparation of Electrolyte>

[0117] In an environment where the water content is less than 10ppm, non-aqueous organic solvents of propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) are mixed in a weight ratio of 1:1:1, and then lithium hexafluorophosphate (LiPF6) is added to the non-aqueous organic solvent to dissolve and mix evenly. Among them, the molar concentration of LiPF6 in the electrolyte is 1.15mol / L. Based on the total weight of the electrolyte, 2% of fluoroethylene carbonate, 2% of vinylene carbonate, and 1% of vinyl sulfate are added and mixed evenly to form an electrolyte.

[0118] <Preparation of lithium-ion batteries>

[0119] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping, and other processes.

[0120] Example 2 to Example 7

[0121] The preparation method is similar to that of Example 1, except for the element contents and particle sizes of lithium manganese oxide shown in Table 1.

[0122] Example 8

[0123] The preparation method is similar to that of Example 1, except that 850.3 g of trimanganese tetraoxide is used to replace 1000.0 g of manganese dioxide. The differences in other parameters are shown in Table 1.

[0124] Example 9

[0125] The preparation method is similar to that of Example 1, except that a niobium compound Nb2O5 is added to the lithium manganese oxide, the aluminum content in the positive electrode active material layer is adjusted to 1.01%, the sodium content is 0.26%, and the niobium content is 0.09%, and the compaction density of the positive electrode active material layer is adjusted to 3.0 g / cm 3 , except for this, it is the same as Example 1.

[0126] Example 10

[0127] The preparation method is similar to that of Example 9, except for the element contents and particle sizes of lithium manganese oxide shown in Table 1.

[0128] Embodiment 11

[0129] Weigh 203.3 g of lithium carbonate (with a lithium content of 18.71%), 850.3 g of manganese tetraoxide (with a Mn content of 70.82% and a Na content of 0.01%), 19.10 g of aluminum oxide (with an aluminum content of 52.91%), and 2.87 g of niobium pentoxide (with a niobium content of 79.46%), mix them in a high-speed mixer at 300 r / min for 20 min, place the mixture in an air kiln, heat it to 750° C. at 5° C. / min, keep it for 24 h, take it out after natural cooling, and pass it through a 300-mesh sieve to obtain the finished product of lithium manganese oxide (i.e., modified LMO).

[0130] Example 12 to Example 13

[0131] The preparation method is similar to that of Example 11, except for the element contents shown in Table 1 and the particle size of the lithium manganese oxide.

[0132] Example 14 to Example 21

[0133] The preparation method is similar to that of Example 9, except for the element contents and particle sizes of lithium manganese oxide shown in Table 1.

[0134] Embodiment 22

[0135] The positive electrode active material modified LMO (the preparation method is similar to that of Example 9, except for the element content and particle size shown in Table 1) and polycrystalline lithium nickel cobalt manganese oxide (LiNi) with an average particle size of 15.3 μm were prepared. 0.60 Co 0.10 Mn 0.30 O2, recorded as NCM: 15.8 (601030)) to obtain a mixture, and the proportions are made according to the parameters shown in Table 1, so that the molar ratio of nickel to manganese and the molar ratio of cobalt to manganese meet the proportions shown in Table 1. The element content and particle size in the positive electrode active material layer are shown in Table 1. The compaction density of the positive electrode active material layer is 3.3 g / cm 3 , except for this, it is the same as Example 9.

[0136] Example 23 to Example 33

[0137] The preparation method is similar to that of Example 22, except that the parameters such as element content, average particle size of modified LMO, type and average particle size of polycrystalline lithium nickel cobalt manganese oxide, molar ratio of nickel and manganese, and molar ratio of cobalt and manganese are adjusted as shown in Table 1.

[0138] Embodiment 34

[0139] The positive electrode active material modified LMO (whose preparation method is similar to that of Example 11, except for the element content and particle size shown in Table 1) and polycrystalline lithium nickel cobalt manganese oxide (LiNi) with an average particle size of 15.3 μm were prepared. 0.50 Co 0.20 Mn 0.30 O2, recorded as NCM: 15.9 (502030)) was mixed to obtain a mixture. The ratio of LMO to NCM was adjusted so that the molar ratio of nickel to manganese and the molar ratio of cobalt to manganese met the ratio shown in Table 1. The element content and particle size in the positive electrode active material layer are shown in Table 1. Other than this, it is the same as Example 11.

[0140] Embodiment 35

[0141] The positive electrode active material modified LMO (whose preparation method is similar to that of Example 11, except that the element content and particle size are shown in Table 1) is mixed with lithium iron phosphate (abbreviated as LFP) having an average particle size of 1 μm to obtain a mixture. The ratio of LMO to LFP is adjusted so that the molar ratio of iron to manganese satisfies the ratio shown in Table 1. The element content and particle size in the positive electrode active material layer are shown in Table 1. Other than this, it is the same as Example 11.

[0142] Embodiment 36

[0143] The preparation method is similar to that of Example 35, except for the parameters shown in Table 1.

[0144] Embodiment 37

[0145] The positive electrode active material modified LMO (the preparation method is similar to that of Example 9, except for the element content and particle size shown in Table 1), polycrystalline lithium nickel cobalt manganese oxide (LiNi 0.55 Co 0.15 Mn 0.30 O2, recorded as NCM: 16.2 (551530)) and lithium iron phosphate (abbreviated as LFP) with an average particle size of 1 μm are mixed to obtain a mixture, so that the molar ratio of nickel to manganese and the molar ratio of cobalt to manganese meet the ratios shown in Table 1. The element content and particle size in the positive electrode active material layer are shown in Table 1. The compaction density of the positive electrode active material layer is 3.3 g / cm 3 . Other than this, it is the same as Example 9.

[0146] Embodiment 38

[0147] The positive electrode active material modified LMO (the preparation method is similar to that of Example 11, except for the element content and particle size shown in Table 1), single crystal lithium nickel cobalt manganese oxide (LiNi 0.55 Co 0.15 Mn 0.30O2, recorded as NCM: 6.4 (551530)) and lithium iron phosphate (abbreviated as LFP) with an average particle size of 1 μm are mixed to obtain a mixture so that the molar ratio of nickel to manganese and the molar ratio of cobalt to manganese meet the ratios shown in Table 1. Other than this, the same as Example 11.

[0148] Embodiment 39

[0149] The positive electrode active material modified LMO (the preparation method is similar to that of Example 9, except for the element content and particle size shown in Table 1), polycrystalline lithium nickel cobalt manganese oxide (LiNi 0.55 Co 0.15 Mn 0.30 O2, recorded as NCM: 16.2 (551530)) and lithium iron phosphate (abbreviated as LFP) with a particle size of 1 μm are mixed to obtain a mixture so that the molar ratio of nickel to manganese and the molar ratio of cobalt to manganese meet the ratios shown in Table 1. Other than this, the rest is the same as Example 9.

[0150] Example 40 to Example 41

[0151] The preparation method is similar to that of Example 39, except for the parameters shown in Table 1.

[0152] Comparative Example 1

[0153] Except that the positive electrode active material is LiMn2O4 not doped with aluminum, the rest is the same as Example 1.

[0154] Comparative Example 2

[0155] Except that the positive electrode active material is LiMn2O4 not doped with aluminum, the rest is the same as Example 22.

[0156] Comparative Example 3

[0157] Except that the positive electrode active material is LiMn2O4 not doped with aluminum, the rest is the same as Example 37.

[0158] Comparative Example 4

[0159] Except for adjusting the element content of the positive electrode active material as shown in Table 1, the rest is the same as Example 9.

[0160] Comparative Example 5

[0161] Except for adjusting the element content of the positive electrode active material as shown in Table 1, the rest is the same as Example 9.

[0162] Table 1

[0163]

[0164]

[0165] The parameters of the combination of A, B, and C are shown in Table 2:

[0166] Table 2

[0167]

[0168]

[0169] In Tables 1 and 2, “ / ” means not contained or not measured.

[0170] It can be seen from Examples 1 to 8 and Comparative Example 1 that for a lithium ion battery having an aluminum element content of A% and a sodium element content of B% in the positive electrode active material layer, and when 0.01≤A≤2 and 0.001≤B≤1, its 25°C cycle capacity retention rate, 45°C cycle capacity retention rate and storage capacity retention rate are significantly improved, indicating that the lithium ion battery of the present application has excellent cycle performance, especially high temperature cycle performance, and excellent high temperature storage performance.

[0171] It can be seen from Examples 1 to 8 and Comparative Examples 1 to 3 that when the positive electrode active material does not contain the lithium manganese oxide of the present application (such as Comparative Examples 1 to 3), its I(400) / I(111) and I(440) / I(400) are beyond the scope of the present application. However, the lithium ion battery having the I(400) / I(111) and I(440) / I(400) ranges of the present application has excellent cycle performance, especially high temperature cycle performance, and excellent high temperature storage performance.

[0172] It can be seen from Examples 9 to 21 and Comparative Examples 4 to 5 that when the aluminum content in the positive electrode active material is too high (such as Comparative Example 4) or the sodium content is too high (such as Comparative Example 5), its I(400) / I(111) and I(440) / I(400) are beyond the range of this application. However, for lithium-ion batteries with aluminum and sodium content within the range of this application, the 25°C cycle capacity retention rate, 45°C cycle capacity retention rate and storage capacity retention rate are significantly improved.

[0173] From the comparison between Examples 1 to 8 and Examples 9 to 21, it can be seen that when the positive electrode active material layer further contains the niobium element of the present application and the content C% is within the range of the present application, the high temperature storage performance of the lithium ion battery is further improved.

[0174] From the comparison between Examples 9 to 21 and Examples 22 to 34, it can be seen that when the positive electrode active material layer further contains lithium nickel cobalt manganese oxide, the 25°C cycle capacity retention rate, 45°C cycle capacity retention rate and storage capacity retention rate of the lithium ion battery are further improved.

[0175] It can be seen from Examples 22 to 34 that the different weight percentages of cobalt in lithium nickel cobalt manganese oxide have an impact on the cycle performance and high-temperature storage performance of the lithium-ion battery. However, as long as the content of lithium nickel cobalt manganese oxide is within the scope of this application, a lithium-ion battery with excellent cycle performance and high-temperature storage performance can be obtained.

[0176] It can be seen from Examples 37 to 41 that when the positive electrode active material layer further contains lithium iron phosphate, the 25°C cycle capacity retention rate, 45°C cycle capacity retention rate and storage capacity retention rate of the lithium ion battery are further improved.

[0177] The relationship between the aluminum content, the sodium content and the niobium content, that is, the A+B value, the A / B value, the A+C value, the A+B+C value and the C / B value, usually also affects the cycle performance and high-temperature storage performance of the lithium-ion battery. It can also be seen from Examples 1 to 41 that as long as the parameters of the combination of the above A, B and C are within the scope of this application, a lithium-ion battery with excellent cycle performance and high-temperature storage performance can be obtained.

[0178] The particle size of the modified LMO, the particle size of the NCM, the particle size of the LFP, the content of Co in the positive electrode active material layer, the molar ratio of Ni to Mn, the molar ratio of Co to Mn, the molar ratio of Fe to Mn and the compaction density of the positive electrode active material layer will generally also affect the cycle performance and high temperature storage performance of the lithium ion battery. It can also be seen from Examples 1 to 41 that as long as the above parameters are within the scope of this application, a lithium ion battery with excellent cycle performance and high temperature storage performance can be obtained.

[0179] Figure 1 This is the XRD diagram of the positive electrode sheet powder of Example 35 of the present application, from Figure 1 It can be seen that the positive electrode active material of the present application has a first diffraction peak corresponding to the (111) crystal plane at 18° to 20°, a second diffraction peak corresponding to the (400) crystal plane at 43° to 45°, and a third diffraction peak corresponding to the (440) crystal plane at 63° to 65°, satisfying 0.25﹤I(400) / I(111)﹤0.5, 0.35﹤I(440) / I(400)﹤0.55.

[0180] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrochemical device comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises lithium manganese oxide, wherein the lithium manganese oxide comprises aluminum and sodium, and based on the weight of the positive electrode active material, the aluminum content is A%, the sodium content is B%, and 0.01≤A≤2, 0.001≤B≤1 is satisfied; The positive electrode active material layer further comprises lithium nickel cobalt manganese oxide, and the weight percentage of the cobalt element is less than or equal to 15% based on the weight of the positive electrode active material.

2. The electrochemical device according to claim 1, wherein at least one of conditions (a) or (b) is satisfied: (a) 0.011≤A+B≤2.5; (b)0.1≤A / B≤125.

3. The electrochemical device according to claim 1, wherein 0.03≤A+B<2, 2<A / B≤125. 4 . The electrochemical device according to claim 1 , further comprising niobium element, wherein the content of the niobium element is C % based on the weight of the positive electrode active material, and satisfies 0<C≤1.

5. The electrochemical device according to claim 4, wherein at least one of conditions (c) to (d) is satisfied: (c) 0.011﹤A+C≤2.8; (d) 0.011≤A+B+C≤3.3; (e)0﹤C / B≤40. The electrochemical device according to claim 4 , wherein 0.07≤A+C≤2.

3.

7. The electrochemical device according to claim 1, wherein: Using XRD testing, the lithium manganese oxide satisfies at least one of the conditions (f) to (g): (f) the lithium manganese oxide has a first diffraction peak corresponding to the (111) crystal plane at 18° to 20°, and the peak intensity of the first diffraction peak is I(111); (g) the lithium manganese oxide has a second diffraction peak corresponding to the (400) crystal plane at 43° to 45°, and the peak intensity of the second diffraction peak is I(400); (h) The lithium manganese oxide has a third diffraction peak corresponding to the (440) crystal plane at 63° to 65°, and the peak intensity of the third diffraction peak is I(440).

8. The electrochemical device according to claim 7, satisfying at least one of the conditions (i) to (j): (i)0.25﹤I(400) / I(111)﹤0.55; (j)0.35﹤I(440) / I(400)﹤0.

55.

9. The electrochemical device according to claim 1, wherein: The molar ratio of nickel element to manganese element in the positive electrode active material layer is 0.02:1 to 0.7:1, and the molar ratio of cobalt element to manganese element is less than or equal to 0.3:

1.

10. The electrochemical device according to any one of claims 1 to 9, wherein: The positive electrode active material layer further comprises lithium iron phosphate, wherein the average particle size of the lithium iron phosphate is smaller than the average particle size of the lithium manganese oxide.

11. The electrochemical device according to claim 10, wherein: The molar ratio of the iron element to the manganese element in the positive electrode active material layer is 0.02:1 to 0.25:

1.

12. The electrochemical device according to claim 10, wherein: Based on the weight of the positive electrode active material layer, the weight percentage of lithium iron phosphate is ≤30%.

13. The electrochemical device according to claim 1, wherein The compaction density P of the positive electrode active material layer is 2.7 g / cm 3 ≤P≤4.0g / cm 3 .

14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Method for preparing lithium manganese oxide cathode material by synergistically doping aluminum and sodium with high rate performance

    CN105428641A

  • Single-particle lithium manganate positive electrode material and preparation method thereof

    CN112993236A

  • Positive electrode material for lithium battery, preparing method thereof and lithium battery

    WO2012159253A1

  • Positive electrode material comprising lithium manganese positive electrode active material having spinel structure, positive electrode and lithium secondary battery

    WO2019088806A1